STRATEGI DAN BAURAN PEMASARAN BAGI PEDAGANG KUE CINCIN DI BARABAI - Muhammad Maladi; Melda Sari; Nirza Marzuki Husein; Henny Septiana Amalia; Abdul Kadir; Dini Rusqiati; Iqbal Firdaus; Rio Adi Saputra; Ahmad Raihan; Punda Susanto; Nikita Laurencia (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The large number of various types of food from other regions makes local food threatened, not to mention the traditional food from other regions in Indonesia which is no less delicious. Many types of food that we used to be able to enjoy are now getting hard to find and the younger generation now don't even know about this type of food. Serious efforts are needed from the government, universities and from the community itself to preserve the local specialties. In order to preserve and develop the regional food, the STIE Indonesia Banjarmasin lecturer team took the time to visit the Hulu Sungai Tengah area, precisely in Barabai City, which is about 150 km away, to do community service by sharing knowledge about entrepreneurship and marketing. The STIE Indonesia Banjarmasin lecturer team conducted a preliminary survey to find out the needs and problems faced by the traders, and continued with brainstorming about the marketing problems they face in the field. After listening to the facts in the field and discussing the problems they face, namely: proposing proposals for capital assistance, providing different flavors, Improving packaging materials and designs by branding, promoting using social media and adding retail points